DELIK DAN SANKSI KESUSILAAN DALAM KUHP INDONESIA DAN SINGAPURA - Pustikasari, Rani Suryani (LPPM Unisba, 2010)
The Indonesian Penal code and Penal Code of Singapore contain the criminal act provisions of decency offence. Decency offence under Indonesian penalcode is categorized according to criminal serious and minor offences. The decency offence sanction is regulated by Book II, Chapter XIV and Book III Chapter VI respectively. In the meantime, decency offence and its criminal sanction under Singaporean Penal code are set out in Chapter XIV entitled: Offences Affecting the Public Health, Safety, Convenience, Decency dan Morals; Chapter XVI on The Offences Affecting Human Body and Chapter XX concerning Offences Relating to Marriage. This article examine a comparative study of decency offence and its criminal sanction under Indonesian and Singaporean Penal Code. It finds that there is similarity between Indonesian and Singaporean Penal Code with regard to the types of criminal acts of decency, rape, adultery, incest,pornography among other thngs. The difference lies in argument and sanction